Analisis Kesulitan Belajar dan Self Confidence Anak Berkebutuhan Khusus Slow Learner dalam Pembelajaran Matematika Kelas Tinggi - Bahri, Syaeful; Nurhayati, Siti; Syifandini, Yufliha (MASALIQ, 2022)
This research aims to provide an overview of learning difficulties in mathematics and self-confidence in children with special needs slow learner in inclusive schools. The location of this research is SDN Kalideres 06, West Jakarta. This research uses a descriptive qualitative method with the subjects assigned are 5 students with special needs in the Slow Learner from each high class in the school, namely grades IV, V, and VI. From the results of this study, it was found that the lack of attention during the learning process and less creative learning methods were the factors that caused slow learner to have difficulty in participating in learning followed by low self-confidence. There is a fact that students with special needs are very difficult to have a high level of self-confidence. The student will not have a level of optimism when receiving criticism.